SICK GIRLS: GENDER, DISABILITY, AND CYBORG HOAXES - Elicessor, Elizabeth (AoIR Selected Papers of Internet Research, 2015)
The story, told and retold, has become an academic urban legend. Its outline is as follows: a male psychiatrist, Alex, entered online spaces under an assumed identity as a woman with a disability, “Joan,”described by Sherry Turkle as “severely handicapped and disfigured,” and unable therefore to leave the house or meet people in person,and by Jodi O'Brien as having damaged “speech and motor coordination.”3 “Joan” conversed with and gained the trust of many women, offered therapy, and engaged in cybersex or set up dates between these women and her “friend” Alex. Eventually, the strain of passing under an assumed identity became too much for Alex, who decided to kill “Joan.” When he posted that she was ill, those who befriended her attempted to contact hospitals and send their condolences, only to find that she did not exist. Those who considered Joan a friend experienced shock, betrayal and outrage at the deception. As an urban legend—always a moralizing genre—the lesson is clear. We must be wary of the truthfulness of those we encounter online, as they may easily be deceptive. Although many internet scholars took up the case of “Joan” in relation to gender, sexuality, postmodern identity and online disembodiment, analysis of the place of disability was sorely lacking.This cyborg hoax—linking embodiment, gender, technology, representation, emotion, and data—was equally indebted to ideologies of ability that figure disability as deficit to be “cured” through technology or other interventions. Gerard Goggin and Christopher Newell refer to a “lacuna” within internet studies where disability is concerned; this paper combines a critical review of internet studies literature featuring “Joan” with theories of normalcy drawn from disability studies and with contemporary cases of gender and disability deception. Ultimately, I argue that disability may be used as a category of critical analysis through which it is possible to resist the normalizing pressures of new media interfaces and structures, and to theorize new media in its variable configurations rather than through generalities.